Investigation on mechanical properties of graphene-polyurethane nanocomposites. Issue 1 (February 2021) - Abbas, S A; Younas, T; Asadullah; Anwar, M A
Abstract: Polymer nanocomposites are increasingly used in applications because of their improved mechanical properties compared to traditional polymers. Graphene has attracted considerable attraction as a reinforcing material in polymers in recent years due its extraordinary effect on enhancing mechanical properties of polyurethane. This paper presents the development and characterisation of mechanical properties of graphene based polyurethane nanocomposites. The yield of the graphene nano material was carried out by using the technique called liquid exfoliation as the use of N-Methyl-2-Pyrollidone (NMP) and Tetrahydrofuran (THF) solvent. Granules polyurethane was converted into blend polyurethane by heating at 100°C and then graphene nano particles were fused with pure polyurethane matrix with different percentage weight of graphene (0, 0.1, 0.3, 0.5 and 0.7 wt.%). Microstructural and Mechanical characterisation of graphene/polyurethane nano-composite matrix were carried out involving Atomic Force Microscopy (AFM), X-Rays Diffraction (XRD) and Universal Testing Machine (UTM) and results were compared with pure polyurethane. The results have shown drastic improvements in mechanical properties with modulus of elasticity increasing by 320% and elongation at breaking point increased by 134% with just 0.7 wt. % of graphene concentration as compared to those of pure polyurethane sample.